2019
DOI: 10.1111/clr.13486
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic inflammation in periimplant and periodontal disease: A case–control split‐mouth study

Abstract: Objective: Although the regulatory effects of substance-P (SP), neurokinin-A (NKA), calcitonin gene-linked peptide (CGRP) and neuropeptide-Y (NPY) on periodontal inflammatory responses have been described, the effects of these neuropeptides on healthy and diseased periimplant tissues are not clearly defined. Materials and methods:Thirty-nine implants loaded at least for 12 months with their symmetrically matching teeth were evaluated and compared by a split-mouth study design. Six study groups were created in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Studies have shown that smokers with periodontitis had higher SP in the gingival biopsy sample than smokers with periodontally healthy teeth, nonsmokers with periodontitis, and nonsmokers with periodontally healthy teeth [23]. Sert et al had seen similar findings where SP levels were higher in the diseased state than in healthy periodontium [25]. In a cross-sectional study, Hanioka et al found that SP was significantly correlated to probing pocket depth (r=0.637, p≤.001), therefore, SP could be a key element in GCF [31].…”
Section: Periodontitis and Spmentioning
confidence: 92%
See 4 more Smart Citations
“…Studies have shown that smokers with periodontitis had higher SP in the gingival biopsy sample than smokers with periodontally healthy teeth, nonsmokers with periodontitis, and nonsmokers with periodontally healthy teeth [23]. Sert et al had seen similar findings where SP levels were higher in the diseased state than in healthy periodontium [25]. In a cross-sectional study, Hanioka et al found that SP was significantly correlated to probing pocket depth (r=0.637, p≤.001), therefore, SP could be a key element in GCF [31].…”
Section: Periodontitis and Spmentioning
confidence: 92%
“…Outlines of the available studies are presented in Table 3 [ 19 - 25 ], Table 4 [ 26 - 28 ], Table 5 [ 29 - 30 ], and Table 6 [ 31 - 32 ]. Several studies analyzed the relationship between periodontal disease and more than one neuropeptide.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations